2016
DOI: 10.1016/j.postharvbio.2016.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chitosan– Aloe vera coating on postharvest quality of blueberry ( Vaccinium corymbosum ) fruit

Abstract: A B S T R A C TThe present study was carried out to evaluate the effect of chitosan-based edible coatings with Aloe vera extract on the postharvest blueberry fruit quality during storage at 5 C. Firstly, A. vera fractions (pulp and liquid) were extracted from leaves and evaluated in terms of antifungal and antioxidant capacities. The choice of the most adequate chitosan and A. vera fraction concentrations to be incorporated in coating formulation was made based on the wettability of the corresponding coating s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
138
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(164 citation statements)
references
References 40 publications
(61 reference statements)
20
138
0
6
Order By: Relevance
“…Moringa plant extracts had a significant effect on the growth rate of C. gloeosporiodes, A. alternata and L. theobromae, a fact that can be closely linked to the high concentration of phenolic compounds in the tissue [58]. B. cinerea and P. expansum were better inhibited than A. niger in the presence of pulp or liquid fractions of A. vera [41]. Aloe vera gel was also effective at controlling the growth of several fungi, exhibiting the greatest efficacy against F. oxysporum.…”
Section: Antifungal Coatings For Fruit Preservationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moringa plant extracts had a significant effect on the growth rate of C. gloeosporiodes, A. alternata and L. theobromae, a fact that can be closely linked to the high concentration of phenolic compounds in the tissue [58]. B. cinerea and P. expansum were better inhibited than A. niger in the presence of pulp or liquid fractions of A. vera [41]. Aloe vera gel was also effective at controlling the growth of several fungi, exhibiting the greatest efficacy against F. oxysporum.…”
Section: Antifungal Coatings For Fruit Preservationmentioning
confidence: 99%
“…[41] Lemongrass essential oil Colletotrichum capsici Inoculation of 10 µL of 10 5 spores/mL, before coating application CH Green bell pepper EO was found to be less effective in vivo than in vitro, but the combination of EO with CH did enhance the antimicrobial activity of the coating.…”
Section: A Ch Smentioning
confidence: 99%
“…It is well known that chitosan can interfere directly with fungal growth and activate several biological processes in plant tissues and is a potential elicitor of plant defenses (El Ghaouth et al, ). Chitosan‐based coatings have demonstrated superior effectiveness for controlling weight loss in lots of studies on blueberry, being a barrier to water transport and having antimicrobial activity (Sun et al, ; Vieira et al, ; Yang et al, ). Blueberry leaf extract incorporating with chitosan coating could maintain high nutritional value in fresh blueberries (Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan-based coatings have demonstrated superior effectiveness for controlling weight loss in lots of studies on blueberry, being a barrier to water transport and having antimicrobial activity (Sun et al, 2014;Vieira et al, 2016;Yang et al, 2014). Blueberry leaf extract incorporating with chitosan coating could maintain high nutritional value in fresh blueberries (Yang et al, 2014).…”
mentioning
confidence: 99%
“…In fact, these coatings are able to reduce gas exchange between food products and the environment, which may decrease respiration rates and thereby delay ripening and senescence of fresh produce in a similar way to storage under modified/controlled atmosphere (Janjarasskul and Krochta ). Several studies have demonstrated the ability of polysaccharide‐based coatings carrying different natural antimicrobial agents to preserve quality and increase safety of many fresh and minimally processed fruits such as orange (Aloui and others ), mango (Cissé and others ), strawberry (Duran and others ), grape (Aloui and others ), blueberry (Vieira and others ), minimally processed papaya (Narsaiah and others ), fresh‐cut pineapple (Azarakhsh and others ), and fresh‐cut apple (Chiabrando and Giacalone ). Likewise, different natural antimicrobial agents mainly EOs have shown potential, when added to edible coating formulations, for prolonging the shelf life of chicken meat (Fernández‐Pan and others ; Bazargani‐Gilani and others ) and seafood products (Asįk and Candoğan ) by reducing oxygen and moisture transmission, limiting microbial contamination and discoloration, and preserving texture, color, and flavor (Gennadios and others ).…”
Section: Introductionmentioning
confidence: 99%